SAT0389 Mri predictive factors for positive ct-guided biopsy in suspected septic spondylodiscitis. (12th June 2018) - Chotard, E.; Jacquier, H.; Richette, P.; Rioux, C.; Joly, V.; Palazzo, E.; Forien, M.; Jelin, G.; Yazdanpanah, Y.; Dieudé, P.; Ottaviani, S.
Abstract : Background: Septic spondylodiscitis is an infection involving intervertebral disc and adjacent vertebral endplates that could lead to neurological complications. Magnetic resonance imaging (MRI) is the main imaging modality to suspect spondylodiscitis. However, MRI features predictive for septic spondylodiscitis are still lacking. Objectives: To assess the MRI features associated with microbial pathogen detection by CT-guided biopsy among patients with suspected septic spondylodiscitis. Methods: Between May 2007 and July 2017, we retrospectively analysed patients who underwent MRI and CT-guided biopsy for suspicion of septic spondylodiscitis. Baseline clinical and biological characteristics were collected. MRIs were analysed by one physician blinded to clinical data. The following MRI features were assessed when available: oedema or contrast-enhancement of intervertebral disk, adjacent vertebrae, epidural and paravertebral space, presence of abscess and paravertebral oedema size. A positive biopsy was defined by pathogen identification on culture or by direct microscopy examination. Results: Fifty-one patients (54.9% of males, mean ±SD age of 59.2±19.1 years) were analysed. Lumbar spine (n=38) was the most affected site. A total of 26 (51%) patients had a CT-guided biopsy positive for a bacterial pathogen, mainly mycobacterium tuberculosis (n=7) and staphylococcus aureus (n=7). Disc size reduction, more than 50% of endplate oedema, loss of intradiscal cleft and abscess were the MRI findings associated with detection of bacterial pathogen by biopsy with a frequency of 100%, 92%, 81% and 50%, respectively. Size of paravertebral oedema was statistically higher in positive CT-guided biopsy than those negative (20.5±12.6 vs . 11.0±9.8 mm, p=0.004). The highest specific MRI finding for bacterial pathogen detection was the presence of paravertebral abscess (80%). Conclusions: Our study showed that loss of intradiscal cleft, abscess and a large endplate oedema were the best predictive factors for a positive CT-guided biopsy. Size of paravertebral oedema is also associated with detection of bacterial pathogen. Physician must be aware of these MRI findings to better determine which patients should have a CT-guided biopsy. Disclosure of Interest: None declared